STUDI KOMPARASI MODEL PEMBELAJARAN TWO STAY TWO STRAY DENGAN METODE DISKUSI DAN MODEL DIRECT INTRUCTION DENGAN METODE RESITASI BERBANTUAN BUKU SAKU TERHADAP AKTIVITAS DAN HASIL BELAJAR KOGNITIF SISWA - Iim Inayah; Nur Khoiri (Universitas PGRI Semarang, 2013)
It has been conducted research to compare student’s activity and cognitive learning outcomes between learning model of Two Stay Two Stray with discussion method and learning model of Direct Instruction with recitation aided pocket book. This research was implemented in MTs 01 Ar-Rohman Bulu at school year of 2012/2013 with cluster random sampling technique. This research design is Quasi Experiment, where the two sample given the different treatment. Data of student’s activity were obtained from observation result and data of student’s cognitive learning outcomes were obtained from pre-test and post-test value. Final analysis using t – test (two part) and comparison test (gain normalized). Based on research result obtained that class using learning model of TSTS with discussion method has percentage of student’s activity classically and exhaustiveness of student’s learning outcomes higher than the learning model of Direct Instruction with recitation method aided pocket book. Result of t – test analysis was showed t count > t table, this is show that there are difference of student’s activity and cognitive learning outcomes between learning model of Two Stay two Stray with discussion method and learning model Direct Instruction with recitation method aided pocket book. Result of gain normalized test obtained value of 0,67 and 0,60, so that the two class are in “medium” category. Based on research result of comparison study of TSTS learning model with discussion method and Direct Instruction learning model with recitation method can increase student’s activity and cognitive learning outcomes in material of Newton’s Law in MTs Ar-Rohman Bulu at school year of 2012/2013.